Chlamydia pneumoniae IgA titres and coronary heart disease; prospective study and meta-analysis. - Danesh, J; Whincup, P; Lewington, S; Walker, M; Lennon, L; Thomson, A; Wong, Y; Zhou, X; Ward, M (2002)
AIMS: To examine associations between Chlamydia pneumoniae IgA titres and incident coronary heart disease, and to compare them with associations previously reported between C. pneumoniae IgG titres and coronary heart disease. METHODS AND RESULTS: We measured serum concentrations of C. pneumoniae IgA antibodies in 502 coronary heart disease cases and in 1005 age- and town-matched controls 'nested' in a community-based prospective study of 5661 British men (mean follow-up in controls, 16 years), and conducted a meta-analysis of published prospective studies to place our findings in context. Two hundred and twenty-one (44%) of the cases were in the top third of C. pneumoniae IgA titres compared with 336 (33%) of the controls, yielding an odds ratio for coronary heart disease of 1.84 (95% confidence interval 1.40-2.43) which was largely unchanged after adjustment. In aggregate, the present study and nine previously reported prospective studies of C. pneumoniae IgA titres involved 2283 cases, yielding a combined odds ratio for coronary heart disease of 1.25 (1.03-1.53), with no significant heterogeneity among the ten studies (chi(2)9=7.8; P>0.1). This combined odds ratio is compatible with that previously reported for C. pneumoniae IgG titres and coronary heart disease (1.15, 0.97-1.36). CONCLUSION: Neither C. pneumoniae IgA titres nor IgG titres are strongly predictive of coronary heart disease in the general population.